2023
DOI: 10.1021/acs.jmedchem.2c01924
|View full text |Cite
|
Sign up to set email alerts
|

A Clinically Translatable Ternary Platinum(IV) Prodrug for Synergistically Reversing Drug Resistance  

Abstract: Scalable production of a clinically translatable formulation with enhanced therapeutic efficacy against cisplatin-resistant tumors without the use of any clinically unapproved reagents and additional manipulation remains a challenge. For this purpose, we report herein the construction of TPP-Pt-acetal-CA based on all commercially available, clinically approved reagents consisting of a cinnamaldehyde (CA) unit for reactive oxygen species generation, a mitochondrially targeted triphenylphosphonium (TPP)-modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Thereafter, the mitochondria-dependent apoptosis-related proteins in the initiation and execution of apoptosis were verified via Western blotting assays. Results in Figure A,B revealed that 14a and combination group ( 14a + CDDP) up-regulated the expression of the pro-apoptotic protein Bax, but down-regulated that of anti-apoptotic protein Bcl-2, which subsequently promoted the release of cytoplasmic Cyt c. By comparison with untreated group, CDDP showed moderate effects on levels of Bax and Bcl-2, which was in accordance with our and others’ reports. ,, Especially, 16a demonstrated more effective than CDDP, 14a , or their combination in activating mitochondrial apoptotic pathway signaling transduction, as evidenced by higher expression levels of pro-apoptotic proteins and cleaved caspase-9 and -3. Furthermore, the severe DNA damage induced by 16a was validated by significant up-regulation of cleaved PARP, whereas CDDP only showed moderate effect as compared with control group (Figure A,B).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Thereafter, the mitochondria-dependent apoptosis-related proteins in the initiation and execution of apoptosis were verified via Western blotting assays. Results in Figure A,B revealed that 14a and combination group ( 14a + CDDP) up-regulated the expression of the pro-apoptotic protein Bax, but down-regulated that of anti-apoptotic protein Bcl-2, which subsequently promoted the release of cytoplasmic Cyt c. By comparison with untreated group, CDDP showed moderate effects on levels of Bax and Bcl-2, which was in accordance with our and others’ reports. ,, Especially, 16a demonstrated more effective than CDDP, 14a , or their combination in activating mitochondrial apoptotic pathway signaling transduction, as evidenced by higher expression levels of pro-apoptotic proteins and cleaved caspase-9 and -3. Furthermore, the severe DNA damage induced by 16a was validated by significant up-regulation of cleaved PARP, whereas CDDP only showed moderate effect as compared with control group (Figure A,B).…”
Section: Resultssupporting
confidence: 89%
“…Previously, we and other researchers had proved that platinum-based anti-cancer agents could disrupt mitochondrial membrane depolarization (ΔΨm) and increase the intracellular ROS accumulation, which were thought to be beneficial for intervening cisplatin resistance. , Moreover, the elevated production of ROS would further promote the collapse of ΔΨm and activate apoptosis-related cascades. Besides, the drug resistance of CDDP in cancer cells frequently occurred along with the decreased effect on promoting ROS generation or regulating expression levels of apoptosis-related proteins. , Therefore, to further investigate whether 16a could initiate mitochondrial apoptotic signaling pathway, we first study the effect of 16a on the changes of intracellular ROS generation via 2′,7′-dichlorofluorescein diacetate (DCFH-DA) staining assays, using 14a , CDDP (5 μM), and combined group ( 14a + CDDP, 5 μM + 5 μM) as references. In line with our and others’ reports, ,, CDDP was not able to increase the production of ROS in PANC-1/CDDP cells as compared with untreated group (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies demonstrated that the loss of MMP is frequently accompanied by the generation of reactive oxygen species (ROS). 58,59 Additionally, a large amount of ROS accumulation in cells could remarkably cause mitochondrial damage, which subsequently leads to tumor cell death. In view of the important physiological functions of ROS, we investigated the ability of the Pt(IV) complex 9 to generate ROS in A549 cells using DCHF-DA staining assays for flow cytometric detection.…”
Section: Complex 9 Induced Cell Apoptosis and Cycle Arrestmentioning
confidence: 99%